Numerical Simulation of Choke Size Optimization in a Shale Gas Well - Jianfa Wu; Xuefeng Yang; Yunting Di; Peiyun Li; Jian Zhang; Deliang Zhang (Geofluids)
To optimize the flowback system of shale gas horizontal wells after fracturing and to maximize the production capacity of gas wells, pipe flow and flowback models of shale gas multistage fractured horizontal wells were established based on the actual geological engineering conditions and the fracture parameters inverted from automatic history matching by combining experimental and numerical simulation methods. Optimization of the maximum choke size, reasonable opening choke size, replacement stages, and choke replacement frequency were studied. The research results show that the larger the production pressure difference in the early period, the higher the initial gas production rate but the easier the migration of proppant and the higher its stress sensitivity, which increases the permeability damage and weakens the reservoir recovery ability. Thus, the fracture conductivity gets worse and the later gas production rate and liquid production rate get lower. Specifically, the research results mainly include the following: (1) The laboratory experiment results show that the effective stress exceeding 19 MPa caused a proppant breakage and embedding phenomenon, leading to difficult recovery from reservoir permeability damage. Therefore, the maximum production pressure difference corresponding to the single-well maximum choke size shall not exceed 19 MPa. (2) A small opening choke size of a shale gas well is superior to the large one, and according to the numerical simulation, the choke size of 3 mm is recommended to be the reasonable opening choke size. (3) Under the drainage and production systems of replacing the choke size from small to large, the simulation results indicate that the production effect under the drainage and production systems of increasing the choke size incrementally stage by stage with an increase in amplitude of 1 mm is much better than that under the drainage and production systems of increasing the choke size by skipping the stage. (4) When the choke size is increased stage by stage, the research results indicate that the optimal duration of each grade of choke size is 3 days, beyond which, the increase of EUR will not be remarkable. The application of the proposed fine choke system research method in Well-CN001 indicates that the influence amplitude of the reasonable choke system on the daily gas production of Well-CN001 is in the range of 65.96%–121.67% and that on single-well EUR increase amplitude in 20 years is in the range of 5.2%–22.27%. The research results provide technical support for understanding the influence of different choke systems on the productivity of shale gas wells and optimizing the reasonable drainage and production systems of shale gas wells after fracturing.